PENGARUH PENGETAHUAN WAJIB PAJAK, KUALITAS PELAYANAN FISKUS, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Aliviany, Delira; Kristianti Maharani, Novera (Pusat Riset dan Inovasi Nasional, 2023)
Tax compliance is an obedient and obedient attitude carried out by taxpayers in carrying out tax obligations. Therefore compliance has always been an important factor in increasing tax revenues as the country's main source of national development. This study aims to analyze the effect of taxpayer knowledge, quality of tax authorities and tax sanctions on individual taxpayer compliance in DKI Jakarta Province. This study uses primary data obtained from respondents' answers to the statements given in the form of a questionnaire. The population of this study is individual taxpayers who have a NPWP and are registered at the KPP DKI Jakarta Administrative City Region. Sampling in this study used a convenience sampling technique which then obtained 100 respondents. The data analysis used in this research is validity and reliability test, descriptive statistical analysis, classic assumption test, and multiple linear regression analysis. Based on the results of the analysis with the help of SPSS software, it shows that taxpayer knowledge has a significant effect on taxpayer compliance, while the quality of tax authorities and tax sanctions do not have a significant effect on taxpayer compliance.